The Peculiarities of Labour Relations Between the Russian IT-Free-Lancers and Their Clients - Валентина Васильевна Вязникова (Journal of Economic Sociology, 2010)
The study is aimed at the analysis of the peculiarities of the labour relations between the Russian IT-free-lancers and their clients as well as at the problems disclosure during their collaboration. The author focuses on hiring process, work conditions, the length of collaboration, work conflicts during the task fulfillment and further development of the labour relations.